Pengembangan Pembelajaran Daring Terintegrasi Media Untuk Mengukur HOTS Mahasiswa Pada Mata Kuliah Kimia Organik - Freddy Tua Musa Panggabean; Jamalum Purba; Marudut Sinaga (Universitas Negeri Medan, 2021)
This research includes development research to produce online learning integrates media of Adobe Flash media and the Articulate Story Line and instruments to measure student HOTS in the General Chemistry study. The development model used refers to the ADDIE development model. The result of this research is that the online learning prototype integrated with Adobe Flash and Articulate Story Line and HOTS instruments is valid and effective. Validity is fulfilled qualitatively by the validators. Effectiveness is fulfilled based on the implementation of learning in an integrated media network that students can access online and proven by the increase in students' ability to complete HOTS instruments with the results of t-test analysis of 26.607 and p = 0.000.